Efficacy and safety of methantheline bromide (Vagantin®) in axillary and palmar hyperhidrosis: results from a multicenter, randomized, placebo‐controlled trial. (25th September 2012) - Müller, C.; Berensmeier, A.; Hamm, H.; Dirschka, T.; Reich, K.; Fischer, T.; Rzany, B.
Abstract: Background  Focal hyperhidrosis can severely affect quality of life. So far, knowledge on the effect of systemic therapy of focal hyperhidrosis is limited. Objective  To assess the efficacy and safety of methantheline bromide (MB) in the treatment of axillary and palmar‐axillary hyperhidrosis. Methods  A multicenter controlled randomized double‐blind clinical trial was conducted in patients with axillary or palmar‐axillary hyperhidrosis defined by a sweat production >50 mg/5 min. Patients received 3 × 50 mg MB daily or placebo over a period of 28 ± 1 days. Main outcome criterion was the reduction of sweat as measured by gravimetry on day 28 ± 1. Quality of life was assessed by Dermatology Life Quality Index (DLQI) and Hyperhidrosis Disease Severity Score (HDSS). Results  A total of 339 patients were randomly assigned to receive MB or placebo. On day 28 ± 1, the mean axillary sweat production was 99 mg for MB and 130 mg for placebo compared with 168 mg and 161 mg respectively at baseline ( P  = 0.004). Patient′s HDSS score decreased in the MB group from 3.2 to 2.4 compared with 3.2 to 2.7 for placebo ( P  = 0.002). Similar results could be obtained for the DLQI with 9.7 for MB and 12.2 for placebo, which decreased from 16.4 or 17 respectively ( P  = 0.003). Tolerability was good for both groups. The most frequent adverse event was dry mouth. Conclusion  Fifty milligrams methantheline bromide three times a day is an effective and safe treatment of axillary hyperhidrosis.